Media Pengembangan Pokari-Dahitu (Pop-Up dan Kartu Ajaib Daur Hidup Tumbuhan) Pada Materi IPA Kelas IV di MI Al-Husna Tenjolaya - Lestari, Hana; Rahmawati, Ima; Arifin, Ghaniyyah Geuliss (EduInovasi: Journal of Basic Educational Studies, 2024)
The purpose of this study was to develop Pokari-Dahitu learning media (Pop-Ups and Plant Life Cycle Magic Cards) in science learning. The type of research used is Research and Development (R&D) using the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). However, this research is limited only at the development stage. This research involved fourth grade MI/SD students at MI Al-Husna Tenjolaya, Bogor Regency. Data collection in this study used interviews and a Likert scale questionnaire (product validation). The data collected was then analyzed descriptively to describe the feasibility of Pokari-Dahitu (Pop-Up and Plant Life Cycle Magic Cards) in science learning. The results of the study showed that (1) the Pokari-Dahitu learning media (Pop-Up and Plant Life Cycle Magic Cards) had never been used before for science learning; (2) Pokari-Dahitu learning media (Pop-Up and Plant Life Cycle Magic Cards) get material validation with a percentage of 93% and media validation with a percentage of 81%, so that it is concluded that the development of powtoon media in mathematics subject matter "circumference and area flat wake" is feasible to use.